2022
DOI: 10.3390/ijerph191710924
|View full text |Cite
|
Sign up to set email alerts
|

Nurses Coping with Stressful Situations—A Cross-Sectional Study

Abstract: Nursing belongs to the group of professions particularly exposed to stress. Since the ability to cope with stress is an important aspect of mental health, the aim of this study was to identify the types of nurses’ behaviours in terms of different coping styles used when dealing with work-related and psychosocial stress. The study was conducted among 1223 Polish nurses by means of a diagnostic survey, using the Coping in Stressful Situations Questionnaire (CISS), the Generalised Self-Efficacy Scale (GSES) and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Nurses belonging to the harmonious type had a higher level of education. The higher the educational level of nurses, the more often they used the task-oriented stress coping style [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nurses belonging to the harmonious type had a higher level of education. The higher the educational level of nurses, the more often they used the task-oriented stress coping style [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…A high sense of self-efficacy is linked to the perception of obstacles arising at work. Such individuals are much better able to cope with difficult situations and improve their skills [10].…”
Section: Discussionmentioning
confidence: 99%
“…The research among active nurses and nursing students primarily concerned the relationship between GSE and the ability to cope with stress. In these studies, it was shown that people with a higher level of self-efficacy were more resistant to stress and coped better in difficult situations, because they used effective coping strategies more frequently [8,12,21,32]. Sense of self-efficacy was also found to be related to the quality of sleep and adherence to the Mediterranean diet among Spanish nursing students [33].…”
Section: Introductionmentioning
confidence: 97%
“…On the other hand, the environment of health care workers, including nurses, has a high level of knowledge about the determinants and threats to health, and can participate in the health education of patients, influencing the modification of their health behaviors [9,10]. In research on the subject, the need to implement health promotion strategies has been demonstrated, including coping with stress, improving mental and physical health as well as quality of life among nursing staff [11,12]. In studies, the prevalence of nutritional errors has been shown as well as other anti-health behaviors that reduce the health potential of health-care workers, including nurses, doctors and students of medical faculties, those with exposure to psychological stress, low levels of physical activity, bad eating habits and other lifestyle aspects [5,6,8,[11][12][13][14][15][16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%